Robinson Crusoe - Defoe, Daniel, 1661?-1731. (Guwahati : LBS Publications, 2008)
As the sole survivor of a shipwreck, an Englishman lives for nearly thirty years on a deserted island.
Keywords: Crusoe, Robinson (Fictitious character) -- Fiction; Shipwrecks -- Fiction; Survival -- Fiction